Colonisation d'un nouvel habitat par Culex pipiens (Diptera, Culicidae) : le creux d'arbre des subéraies en pays Zaer, Maroc (Annales de Limnologie - International Journal of Limnology, 1989)
The dry conditions which occurred in Morocco from 1981 to 1983 have resulted in the selection of a new habitat by Culex pipiens, which is a very adaptable species, in hollows of trees. Morphological descriptions of the fourth larval instar, the pupae and the male and female adults have shown that these populations living in iree holes (phytotelmata) belong to the form C. pipiens autogenicus.